The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/nar/gkn552
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DNA ligase IV prevents recognition of DNA by double-strand break repair proteins XRCC4 and XLF

Abstract: The repair of DNA double-strand breaks by nonhomologous end-joining (NHEJ) is essential for maintenance of genomic integrity and cell viability. Central to the molecular mechanism of NHEJ is DNA ligase IV/XRCC4/XLF complex, which rejoins the DNA. During adenovirus (Ad5) infection, ligase IV is targeted for degradation in a process that requires expression of the viral E1B 55k and E4 34k proteins while XRCC4 and XLF protein levels remain unchanged. We show that in Ad5-infected cells, loss of ligase IV is accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…In addition to Ku70 and DNA-PKcs, XRCC4 forms a tight complex with Ligase IV, leading to DNA-end joining [35]. XRCC4 is recruited to the DSBs and phosphorylated by DNA-PK [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Ku70 and DNA-PKcs, XRCC4 forms a tight complex with Ligase IV, leading to DNA-end joining [35]. XRCC4 is recruited to the DSBs and phosphorylated by DNA-PK [36].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant progress demonstrating how XLF and XRCC4 regulate Ligase IV function, little is known about how Ligase IV regulates NHEJ. It has been shown that proteasome mediated degradation of Ligase IV prevents the binding of XRCC4 and XLF to DNA, without changing their protein levels (13). DNA binding by XRCC4 and ligation activity of the complex was restored following complementation with the full length Ligase IV (13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that proteasome mediated degradation of Ligase IV prevents the binding of XRCC4 and XLF to DNA, without changing their protein levels (13). DNA binding by XRCC4 and ligation activity of the complex was restored following complementation with the full length Ligase IV (13). Independent studies showed that localization of XRCC4 and XLF to chromatin was also dependent on Ligase IV (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The ATR arm of the DDR is targeted during adenovirus serotype 12 infections by E4 orf 6-mediated degradation of TOPBP1 independently of E1B-55K (Blackford et al, 2010) and by the E1B-55K-associated protein 5 (E1B-AP5) and its ability to promote phosphorylation of ATR substrates. The NHEJ arm of the DDR is targeted by E4 orf 6 in complex with E1B-55K through the degradation of DNA ligase IV (Baker et al, 2007) and independently of E1B-55K by disrupting the association of XRCC4 with DNA ligase IV, thus precluding binding to DNA (Jayaram et al, 2008a; Jayaram et al, 2008b). E4 orf 6 also inhibits protein phosphatase 2A (PP2A) leading to the sustained phosphorylation of DNA-PK and H2AX with hyperactivation of the DDR in response to ionizing radiation (Hart et al, 2007; Hart et al, 2005).…”
Section: Introductionmentioning
confidence: 99%